2023
DOI: 10.1038/s41541-023-00647-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a Trypanosoma cruzi cyclophilin-19 deletion mutant protects against acute Chagas disease in mice

Abstract: Human infection with the protozoan parasite Trypanosoma cruzi causes Chagas disease for which there are no prophylactic vaccines. Cyclophilin 19 is a secreted cis-trans peptidyl isomerase expressed in all life stages of Trypanosoma cruzi. This protein in the insect stage leads to the inactivation of insect anti-parasitic peptides and parasite transformation whereas in the intracellular amastigotes it participates in generating ROS promoting the growth of parasites. We have generated a parasite mutant with depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Several vaccines against T. cruzi have been pre-clinically tested in animal models, using different antigens and platforms. Most assayed antigens are well-characterized parasite virulence factors belonging to large multigene families, such as trans -sialidase, ASP-2, and cruzipain ( Tzelepis et al., 2008 ; Haolla et al., 2009 ; Bontempi et al., 2015 , 2017 ; Cerny et al., 2020 ; Moraschi et al., 2021 ; Castro et al., 2023 ; Jha et al., 2023 ). However, to date, none antigen-defined vaccines have been able to induce an immune response that avoids an initial infection with the parasite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several vaccines against T. cruzi have been pre-clinically tested in animal models, using different antigens and platforms. Most assayed antigens are well-characterized parasite virulence factors belonging to large multigene families, such as trans -sialidase, ASP-2, and cruzipain ( Tzelepis et al., 2008 ; Haolla et al., 2009 ; Bontempi et al., 2015 , 2017 ; Cerny et al., 2020 ; Moraschi et al., 2021 ; Castro et al., 2023 ; Jha et al., 2023 ). However, to date, none antigen-defined vaccines have been able to induce an immune response that avoids an initial infection with the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, special attention has been paid to the use of glycoantigens, chimeric antigens, novel adjuvants, and live platforms ( Nogueira et al., 2013 ; Sanchez Alberti et al., 2017 ; Portillo et al., 2019 ; Bivona et al., 2020 ; Lokugamage et al., 2021 ; Rodrigues da Cunha et al., 2021 ; Cai et al., 2022 ; Pacini et al., 2022 ). Recently, Jha et al. (2023) demonstrated that a parasite attenuated by the deletion of cyclophilin-19 completely prevents T. cruzi infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most CyPs from T. vaginalis retain the aa residues essential for catalytic activity within the highly conserved CLD identified in TvCyP19 (referred to as TvCyP1 by Hsu et al, 2014) [26]: H 62 , R 63 , F 68 , M 69 , Q 71 , G 80 , A 109 , N 110 , A 111 , Q 119 , F 121 , W 129 , L 130 , and H 134 . Exceptions to this pattern were observed in TvCyP21, TvCyP37, and TvCyP44 (Supplementary Figure S2).…”
Section: Trichomonas Vaginalismentioning
confidence: 99%
“…TcCyP19 is also involved in the modulation of ROS production during infection, promoting T. cruzi proliferation [78]. Recently, TcCyP19 has been identified as a promising target of treatment for this disease [134] and seems to be a promising biomarker for evaluating trypanocidal therapies and diagnosing the disease [135].…”
Section: Localization and Functions Of Ppiases In Parasitesmentioning
confidence: 99%